SOSIALISASI PEMBIAYAAN BANK SYARIAH MELALUI PLATFORM DIGITAL - Kartika Marella Vanni (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2022)
The sophistication of information technology today has an important role in all aspects of life and it is undeniable that technology has become something that is very much needed in carrying out daily activities. In the business field, for example, this will also be very influential for someone who has a business, starting from fulfilling capital, creating a product, distribution process, to marketing all require technological intervention. However, with the lack of literacy related to the use of technology from business actors, socialization is needed. The purpose of this service activity is to provide literacy to the community, especially business actors regarding the use of digital platforms in the financing process. This community service activity is carried out in the form of counseling/socialization with the target of the activity being the community of the Ngaliyan sub-district, Semarang city. And found the result that people who are generally dominated by business actors still have very minimal knowledge about the use of digital platforms, they know that the financing process can only be done in the conventional way, namely coming directly to the bank. It is hoped that this activity can add information to the community.